Physicochemical and Antimicrobial Properties and Determination of Phenols and Flavonoids Content of Propolis from Bee Hives in Khorasan Razavi Province - Bi Bi Marzieh Razavizadeh; Razieh Niazmand; Somayeh Hajinezhad; Ehsan Akbari (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2020)
In this research, the physicochemical and antimicrobial properties of propolis from honeybee beehives around Mashhad and the content of active compounds in propolis were determined by high pressure liquid chromatography (HPLC) both quantitatively and qualitatively. Physicochemical properties of the propolis sample (such as ash, moisture, soluble solids and insoluble solids and existing metal elements) were measured. The total phenolic and flavonoids compounds in the ethanolic extract of propolis were 40.126 mg/g (gallic acid) and 26.46 mg/g (quercetin), respectively. Antimicrobial tests showed that the minimum inhibitory concentration (MIC) of the extract against Staphylococcus aureus was 100 mg/mL, while in the applied concentration MIC did not achieve against Escherichia coli. Also, the results of the minimum bactericidal concentration (MBC) test indicated that propolis extract on Staphylococcus aureus had only inhibitory effects. Evaluation of the content of phenolic and flavonoid compounds in propolis extract by HPLC indicated that the flavonoid compounds included flavones (13.33 mg/g), flavonoids (6.375 mg/g), flavonols (8.235 mg/g) and flavanones (16.825 mg/g). Based on the results, propolis can be used in various food and pharmaceutical industries.